Innovations in surgery between the past and future: A narrative review of targeted literature - Obada Hasan; Ahmed Ayaz; Laiba Masood; Abdul Mannan Baig; Naveed Baloch (Journal of the Pakistan Medical Association, 2022)
Innovation is the introduction of a new method or technology designed to change the way things are done. History is full of remarkable innovations in surgery over the years as surgeons have always been innovating and pioneering latest techniques and equipment that can benefit the mankind. Though persistent, progress has been far from uniform. Despite all the bells and whistles that these innovations bring to the table, the little acknowledged fact is that they are only accessible to a very small proportion of the global population. Continuous...